Danger spots of the world - "Newman, Bernard" (London, 1959)
This book covers the danger spots of middle east,Russian and Kurdish claims; French North Africa;China; Japan; South east Asia; Indonesia; India and Pakistan and Poland etc. This book covers the following topics Palestine- the peel commission partition plan,1937; Arab frontiers with Israel today compared with the United Nations 1947 Partition Plan for Palestine; Africa - Black and White; The Curzon and other lines; Races of Poland; The Balkans; Tito's Yugoslavia; Macedonia; The problems of Roumania; Germany; Russia's territorial gains etc.
Keywords: International relations